Simultaneous saccharification and fermentation of sago hampas into biobutanol by Clostridium acetobutylicum ATCC 824 - Husin, Hazwani; Ibrahim, Mohamad Faizal; Kamal Bahrin, Ezyana; Abd Aziz, Suraini (John Wiley & Sons, 2018)
Simultaneous saccharification and fermentation (SSF) by Clostridium acetobutylicum ATCC 824 was conducted to produce biobutanol from sago hampas. Sago hampas is a waste generated from the processing of sago starch. This waste is composed of 54.6% starch and 31.7% of cellulose and hemicellulose, with only 3.3% of lignin. In order to fully utilize the starch and cellulosic materials, saccharification using a mixture of amylase (Dextrozyme) and cellulase (Acremonium cellulase) was conducted using 0.09 g/mL sago hampas, producing 67.0 g/L of fermentable sugar. The SSF and delayed SSF (DSSF) were conducted using 0.07 g/mL sago hampas with the optimized enzyme loading of Dextrozyme amylase (71.4 U/gsubstrate) and Acremonium cellulase (20 FPU/gsubstrate). The SSF of sago hampas generated 6.12 g/L of solvents with biobutanol concentration of 3.81 g/L and the yield of 0.11 g- biobutanol/g- sugar. In order to improve biobutanol concentration and productivity, DSSF was intro-duced. In DSSF, the inoculum was introduced into the system after 24 hour of fermentation to allow the optimal saccharification process for sugar production. This process generated 4.62 g/L of biobutanol which was 18% higher than normal SSF since the saccharification and fermentation were operated at their optimal condition.